The Whitehead journal of diplomacy and international relations
The Journal of Diplomacy and International Relations is the official semiannual publication of the School of Diplomacy and International Relations at Seton Hall University. The Journal provides a unique forum for international leaders in government, the private sector, academia and nongovernmental organizations to analyze and comment on international affairs.